Tradição, religiosidade e pertencimento na performance musical da Folia de Reis da Serra - Rocha, Rosenilha Fajardo (2014)
The Folias de Reis is one of the important cultural manifestations present in Brazil. Inserting within the field of cultural manifestations of Brazilian popular Catholicism, are characterized by joining religious elements, musical, theatrical and plastics. Among the Brazilian states that have the Folias Kings as a living expression of their culture, stands out in this study a reality of the state of Minas Gerais. This work addressed in a specific way the Serra dos Barbosa community, located in the countryside of Leopoldina, which is included in the Forest Zone East of Minas Gerais. This region is an expressive representation of Folias Kings in the state. In this universe, there was a ethnomusicological study of the manifestation of the Folia de Reis da Serra, aiming to present and analyze the key factors which shape and give meaning to the musical performance of this revelry, and these elements tradition, religion and belonging. Through this study it was concluded that the performance of revelry da Serra is characterized by religious-musical aspects that are configured by the addition of music to wider cultural dimensions, including the worldviews and the ethos of the people involved, the social perspectives and the relations surrounding the demonstration. It also covers the rite structures, tradition and own religiosity of the rural community, the "foundation" of revelry and finally the membership of this community to this sound-ritual manifestation. The music of revelry in this universe, incorporates aspects of social relations established among the revelers and assistance in the process of performance. Faith and devotion to the Three Kings of the East explained in musical moments within the sacred universe determine the specific performance evidenced in "snippets" in the "tunes", body movements, and the relationship between performance and the sacred objects and consecrated that makes up the symbolic universe of Folia da Serra. Characteristics, associated with traditional conceptions of a demonstration that preserves significant aspects of their original identities shape the world of Folia de Reis da Serra, cultural context where the revelry performs, ritualized and renews its manifestation in the present. The tradition in which the revelry is inserted, the "foundation" of revelry, the lived religion and the people belonging to this event, determine the particularities of their musical performance and are essential for the existence of revelry and the way in which these people think, feel and live in the world.